Mechanical characterization and preparation of 304 stainless steel for TEM analysis - Yeo, Melvin Chuan Sheng (Nanyang Technological University, 2021)
Laser Shock Peening (LSP) has become a popular form of surface hardening treatment due to its superior properties and improved quality control. It can induce large amounts of compressive stress on the metal surface without damaging the surface integrity. Generally, 304 Stainless Steel (304SS) cannot be strengthened through traditional heat treatment, due to the presence of high nickel content. As a result, the LSP process was one of the prevailing methods used to treat 304SS to obtain superior properties. Ultimately, this project aims to observe the effects and benefits of LSP by conducting several experiments on treated and untreated samples of 304SS. Such experiments include Optical Microscope (OM) test, Transmission Electron Microscopy (TEM) test and Vickers’ Hardness tests. Before the experiments, detailed steps were also done to showcase the complicated sample preparation steps for both OM and TEM analysis. The results from the different tests were tabulated and compared to obtain a proper characterization of the LSP process. Close observations of Optical Micrographs at high magnifications found the formation of ε-Martensites, Stacking Faults and the decrease in grain sizes, which hinders any form of dislocation and led to the improvements in properties. Ultimately, through the Vickers’ Hardness test, LSP was found to improve the surface hardness on not only the peened surface, but also along the depth of the cross-section as well. Challenges raised from sample preparation includes improper handling leading to damaged specimens and improper grinding leading to uneven surfaces. By undertaking this research, the benefits of LSP could be better known to engineers worldwide, such that it could be used in more applications to help improve materials selections, leading to the production of better and stronger structures/equipment.